2013
DOI: 10.1159/000354333
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>CCDC62</i></b> Variant rs12817488 Is Associated with the Risk of Parkinson's Disease in a Han Chinese Population

Abstract: It has been recently proposed by a genome-wide association study (GWAS) meta-analysis that the CCDC62 variant rs12817488 is a new risk locus associated with Parkinson's disease (PD). In this study, we aimed to investigate the association between rs12817488 and PD in a Chinese cohort. A total of 341 PD patients and 423 matched controls were recruited in Eastern China. Our results showed that the A allele of rs12817488 was significantly associated with an aggravated risk of PD (p = 0.006) and represented a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…found there was no association between rs12817488 and PD in a larger cohort [14], but the other group reported that the A allele of rs12817488 was significantly associated with an aggravated risk of PD in Eastern China [15]. In contrast to Liu et al's studies [15], we found that the genotype and allele frequencies of rs12817488 were only associated with the LOPD group and the male patients. Therefore, replication of these studies in Chinese populations is necessary to validate the role of this locus in PD risk.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…found there was no association between rs12817488 and PD in a larger cohort [14], but the other group reported that the A allele of rs12817488 was significantly associated with an aggravated risk of PD in Eastern China [15]. In contrast to Liu et al's studies [15], we found that the genotype and allele frequencies of rs12817488 were only associated with the LOPD group and the male patients. Therefore, replication of these studies in Chinese populations is necessary to validate the role of this locus in PD risk.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that this variant increases the risk of PD by approximately 1.6-fold, which is similar with the reports of other groups [15,17,21]. There are two previous, related studies in the Han Chinese population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yu et al . found that a significant association only existed in males [ 56 ], while Liu et al . only found this association in a female population [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rs12817488 is localized in the intron of Coiled-coil domain containing 62 (CCDC62), and has been found to be associated with PD risk, but the overall and stratified subgroup results were controversial. Yu RL showed significant association only existed in male, while Liu RR found this only in female population 6 7 . However, Li NN found no relationship between rs12817488 and PD susceptibility 8 .…”
mentioning
confidence: 83%